Perancangan Interior Kafe Dan Resto The Historic Of Blitar - Aditya Chandra Puspoyo; Andereas Pandu Setiawan; dody wondo (Intra, 2015)
Nowadays, places like restaurants or café are very popular for middle-upper class and middle-lower class society for meetups, business, or to just simply sit back and relax, even in areas and cities in Indonesia that are still developing, for example; Blitar city. However, in those developing cities, those places are mostly still under-developed, and besides, most of the visitors who came to Blitar are only familiar with the tourists destinations without knowing the origins or the history of Blitar city. Blitar’s interesting heritage of local legends will be relived and applied to the restaurant’s design concept, so this place can also be used as information centre of Blitar, considering the lack of that kind of places in the city. This interior design is also as a renovation for the place with the goal of improving the interior elements and systems that still haven’t expressed the concept of Blitar, therefore, this design will use the concept of “Time Travel” to answer the currently existing problems.